2010 7th IEEE Working Conference on Mining Software Repositories (MSR 2010) 2010
DOI: 10.1109/msr.2010.5463290
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and copying between GNOME projects

Abstract: Abstract-This paper presents an approach to automatically distinguish the copied clone from the original in a pair of clones. It matches the line-by-line version information of a clone to the pair's other clone. A case study on the GNOME Desktop Suite revealed a complex flow of reused code between the different subprojects. In particular, it showed that the majority of larger clones (with a minimal size of 28 lines or higher) exist between the subprojects and more than 60% of the clone pairs can be automatical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…ArgoUML has been used in many previous studies on the evolution of code clones [1,[12][13][14][15]. Besides, other empirical studies have looked at ArgoUML and it can be considered a well-studied system.…”
Section: Study Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…ArgoUML has been used in many previous studies on the evolution of code clones [1,[12][13][14][15]. Besides, other empirical studies have looked at ArgoUML and it can be considered a well-studied system.…”
Section: Study Setupmentioning
confidence: 99%
“…The last change date information from version control systems has been used by Krinke et al [15,16] to compare the history of clone pairs and distinguish the original from the copied code. Their approach is able to do the distinction for the majority of clone pairs even between different projects (they analyzed the subprojects of the GNOME Desktop Suite).…”
Section: Related Workmentioning
confidence: 99%
“…Several studies [18,32,22] have provided evidence for widespread presence of clones and there has been much interest and previous work on software engineering applications and implications such as software evolution [21,36,7,3,29], refactoring [4], and bug detection [24,31,23]. Many tools and techniques for detecting clones have been studied [34].…”
Section: Introductionmentioning
confidence: 99%
“…To copy otherwise, to republish, to post on servers or to redistribute to lists, requires prior specific permission and/or a fee. ESEC/FSE '13, August [18][19][20][21][22][23][24][25][26]2013, Saint Petersburg, Russia Copyright 13 ACM 978-1-4503-2237-9/13/08 ...$15.00.…”
Section: Introductionmentioning
confidence: 99%
“…The presented approach was also used to study how code is copied and cloned between subprojects of the GNOME Desktop Suite [23]. The case study revealed a complex flow of reused code between the different subprojects.…”
Section: Related Workmentioning
confidence: 99%